Clinical evaluation of two packable resin-based composite restorations: A three-year report - Torres, Carlos Rocha Gomes [UNESP]; Barges, Alessandra Buhler [UNESP]; Goncalves, Sergio Eduardo Paiva [UNESP]; Pucci, Cesar Rogerio [UNESP]; De Araujo, Maria Amelia Maximo [UNESP]; Barcellos, Daphne Camara (My University, 2010)
This randomized clinical trial sought to evaluate the performance of two packable composites over a period of 36 months. A total of 39 Class I and II restorations were placed in the permanent teeth of 20 patients. Using United States Public Health Services criteria, two investigators evaluated the restorations immediately after placement and again after 12 and 36 months, examining color match, marginal discoloration, marginal integrity, recurrent caries, proximal contact, anatomical shape, surface texture, and postoperative sensitivity. It was concluded that the packable composites evaluated showed satisfactory clinical performance after three years.
Keywords: Filtek P60 Composite Resin; Prodigy Condensable; resin; adolescent; adult; chemistry; clinical trial; controlled clinical trial; controlled study; dental caries; dental surgery; endodontics; human; longitudinal study; methodology; middle aged; prosthesis; randomized controlled trial; treatment outcome; Adolescent; Adult; Composite Resins; Dental Caries; Dental Marginal Adaptation; Dental Restoration Wear; Dental Restoration, Permanent; Humans; Longitudinal Studies; Middle Aged; Prosthesis Coloring; Treatment Outcome; Young Adult